Are external management consultancies effective in healthcare improvement, do they reflect value for money and what are the alternative models?. Issue 11 (11th November 2019) - Skouteris, Helen; Kirkpatrick, Ian; Currie, Graeme; Braithwaite, Jeffrey; Teede, Helena
Abstract: Despite the increasing use and costs associated with external management consultancy for healthcare improvement, there is a paucity of formal evaluations examining impact. This paper aims to: (i) discuss the potential benefits and disadvantages of external consultancies in addressing complex healthcare challenges and delivering healthcare improvement in Australia; and (ii) explore potential alternative models, including internal consultancy and hybrid models delivered through platforms of collaborative expertise. We propose that the substantive reliance on high cost external management consultancies without demonstrating value or benefit, is unsustainable. An integrative approach that embeds research and capacity building within healthcare services may be of value.